A fast-setting, low-cost, strong integral hydrophobic cement mortar and preparation method thereof

By using lauric acid as a hydrophobic additive, combined with high Belite aluminate cement and standard sand, a fast-set, low-cost and solid overall hydrophobic cement mortar was prepared, which solved the problem of insufficient corrosion resistance of concrete and achieved efficient hydrophobicity and durability.

CN116082005BActive Publication Date: 2025-03-18WUHAN UNIV
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202310099387.X
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-01-31
Publication Date
2025-03-18
Estimated Expiration
2043-01-31

AI Technical Summary

Technical Problem

In the prior art, concrete has insufficient corrosion resistance, resulting in reduced corrosion of steel bars and concrete durability, and commonly used hydrophobic additives have problems such as human health and environmental impacts, and high costs.

Method used

Lauric acid is used as a hydrophobic additive, and fast-set, low-cost, and solid overall hydrophobic cement mortar is prepared by dissolving it in anhydrous ethanol, stirring and ultrasonic dispersing at a specific temperature to form a low-surface energy solution, and then mixing it with high Belite aluminate sulfate cement and standard sand.

Benefits of technology

The superhydrophobicity of cement mortar is achieved, the static contact angle can reach 154.8°, the initial settling time is 27-29min, the final settling time is 33-36min, the immersion water absorption rate is reduced by 77%, and it has good self-cleaning effect and mechanical durability.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN116082005B_ABST
    Figure CN116082005B_ABST
Patent Text Reader

Abstract

The present invention relates to a quick-setting, low-cost, strong integral hydrophobic cement mortar and a preparation method thereof, wherein the preparation method comprises: 1) dissolving lauric acid in anhydrous ethanol and stirring evenly to obtain a lauric acid ethanol solution; 2) adding deionized water to the lauric acid ethanol solution, stirring at 60-65°C for 3-5min, and then ultrasonically dispersing for 30-45min in a temperature environment of 40-55°C to obtain a low surface energy solution; 3) pouring the low surface energy solution into a small agitator equipped with standard sand, stirring for a period of time, adding high Belite aluminate sulfate cement, and then stirring at a low speed for 180-210s, and then stirring at a high speed for 120-150s to obtain a modified cement mortar, pouring it into a mold, and vibrating to remove bubbles; 4) curing and drying the sample obtained in step 3) after demoulding to form a super-hydrophobic cement mortar block. The cement mortar block provided by the present invention has good self-cleaning effect and mechanical durability.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of inorganic non-metallic materials, and in particular to a fast-setting, low-cost, strong integral hydrophobic cement mortar and a preparation method thereof. Background Art

[0002] Concrete has become one of the most widely used building materials in houses, roads, bridges, water conservancy projects, marine engineering, etc. due to its advantages of simple process, low price, abundant raw materials, and excellent mechanical properties. Due to the hydrophilicity of the raw materials and the porosity of the concrete itself, water and corrosive ions in the water (such as Cl - 、SO4 2- , H + Mg 2+ ) can easily penetrate the interior of concrete. A large number of studies have shown that corrosive ions will react with hydration products or steel bars, resulting in reduced durability of concrete and loss of mechanical properties of steel bars. More seriously, corroded steel bars will aggravate the damage of concrete, which has an extremely adverse effect on the safety and service life of buildings. On the other hand, research has investigated and estimated that the cost of dealing with corroded structures is about 3 trillion US dollars per year, accounting for about 3.4% of the global GDP in 2013, and the economic losses caused are huge. Therefore, improving the corrosion resistance of concrete structures has an extremely important impact on engineering safety and national economy.

[0003] Since water is a medium for ion transmission, reducing the permeability of concrete is an effective way to prevent ions from invading concrete and thus improve its corrosion resistance and durability. Inspired by animals and plants in nature, super-hydrophobic surfaces with a water contact angle greater than 150° have received increasing attention due to their complete water repellency, and are of great value in corrosion prevention, drag reduction, and self-cleaning. According to existing studies, there are two main methods for constructing super-hydrophobic surfaces: applying a hydrophobic coating on the surface and constructing an overall hydrophobic structure. The super-hydrophobic surface coating is susceptible to mechanical wear and tear, resulting in super-hydrophobic degradation, which limits its application in practical engineering. Compared with surface hydrophobic modification, even if the overall hydrophobic concrete surface is destroyed, the newly exposed surface is still hydrophobic. Therefore, the long-term hydrophobicity and durability of the overall hydrophobic concrete are much higher than those of the surface hydrophobic concrete. The prior art includes the use of polydimethylsiloxane (PDMS) attached to the pore wall left by the volatilization of octane to achieve super-hydrophobic modification of cement mortar, which has a contact angle of 166°. In addition, fluoroalkyl silane was added during the mixing process to prepare a super-hydrophobic mortar with a contact angle of 158°, and a multi-level rough structure was constructed by covering with a copper mesh. In addition, stearic acid was used as a low surface energy modifier to treat sand and produce super-hydrophobic concrete.

[0004] Although the hydrophobicity and durability of concrete modified with hydrophobic additives are improved, different modifiers have their own limitations. Fluorine-containing modifiers have adverse effects on human health and burden the environment; silane and siloxane are expensive and difficult to be widely used in engineering; stearic acid is cheap and green, but the long carbon chain stearic acid (SA, CH3 (CH2) 16 COOH) requires a relatively high temperature to dissolve in ethanol and is difficult to remain liquid at room temperature, making it difficult to disperse evenly in fresh mortar.

[0005] Therefore, it is urgent to develop new hydrophobic additives that are green, environmentally friendly, inexpensive and simple. Summary of the invention

[0006] In view of the above problems, a quick-setting, low-cost, strong integral hydrophobic cement mortar and a preparation method thereof are provided. The preparation method has the advantages of convenient preparation, low cost, environmental protection, non-toxicity, and quick effect, and provides support for the good application of superhydrophobic materials in the field of building materials.

[0007] The specific technical solutions are as follows:

[0008] The first aspect of the present invention is to provide a method for preparing a fast-setting, low-cost, strong integral hydrophobic cement mortar, which has the following characteristics and comprises the following steps:

[0009] 1) dissolving lauric acid in anhydrous ethanol and stirring uniformly to obtain a lauric acid ethanol solution;

[0010] 2) adding deionized water to the lauric acid ethanol solution obtained in step 1), stirring at 60-65° C. for 3-5 minutes, and then ultrasonically dispersing at a temperature of 40-55° C. for 30-45 minutes to obtain a low surface energy solution;

[0011] 3) pouring the low surface energy solution obtained in step 2) into a small stirrer filled with standard sand, stirring for a period of time, then adding high belite aluminate sulfate cement, stirring at a low speed for 180 to 210 seconds, and then stirring at a high speed for 120 to 150 seconds to obtain a modified cement mortar, pouring it into a mold, and vibrating to remove bubbles;

[0012] 4) After demoulding the sample obtained in step 3), the sample is cured in a standard curing room at 20-25° C. and a relative humidity of 90-95% for 24-72 hours, and then dried in air to form a super-hydrophobic cement mortar block.

[0013] The above preparation method also has the following characteristics: in step 3), the mass ratio of high belite aluminate sulfate cement to lauric acid and anhydrous ethanol in cement mortar is 1:(0.04-0.06):(0.06-0.10), and the water-cement ratio of cement mortar is 0.45-0.50.

[0014] The above preparation method also has the characteristic that, in step 3), the sand-binder ratio in the cement mortar is 0.7-1.

[0015] The second aspect of the present invention is to provide a fast-setting, low-cost, strong integral hydrophobic cement mortar block having the following characteristics and prepared according to the above-mentioned preparation method.

[0016] The beneficial effects of the above scheme are:

[0017] 1) The static contact angle of the cement mortar block provided by the present invention can reach 154.8°; the initial setting time is 27 to 29 minutes, and the final setting time is 33 to 36 minutes;

[0018] 2) The cement mortar block provided by the present invention can reduce the water absorption rate by 77% compared with the unmodified high-belite aluminate sulfate cement mortar;

[0019] 3) The cement mortar block provided by the present invention has good self-cleaning effect and mechanical durability. BRIEF DESCRIPTION OF THE DRAWINGS

[0020] Figure 1 It is a flow chart of the preparation of the integral hydrophobic cement mortar in the embodiment;

[0021] Figure 2 A hydrophobicity test diagram of the super-hydrophobic cement mortar block provided in Example 1;

[0022] Figure 3 A hydrophobicity test diagram of the super-hydrophobic cement mortar block provided in Example 2;

[0023] Figure 4 A hydrophobicity test diagram of the super-hydrophobic cement mortar block provided in Example 3;

[0024] Figure 5 The hydrophobicity test diagram of the ordinary cement mortar block provided for Comparative Example 1;

[0025] Figure 6 The SEM images of the sample surfaces in Example 3 and Comparative Example 1 are compared, wherein (a)-(d) are the surfaces of Comparative Example 1 at different magnifications, (e)-(h) are the surfaces of Example 3 at different magnifications, and (d) and (h) are sand surfaces;

[0026] Figure 7 It is a comparison chart of the immersion water absorption rate of the samples in Example 3 and Comparative Example 1;

[0027] Figure 8 This is a comparison chart of the self-cleaning test effects of the samples in Example 3. DETAILED DESCRIPTION

[0028] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0029] It should be noted that, in the absence of conflict, the embodiments of the present invention and the features in the embodiments may be combined with each other.

[0030] The present invention will be further described below in conjunction with the accompanying drawings and specific embodiments, but they are not intended to limit the present invention.

[0031] Example 1

[0032] A method for preparing a fast-setting, low-cost, strong integral hydrophobic cement mortar, the preparation comprising the following steps:

[0033] 1) Dissolve 1.5 g of lauric acid in 3.75 g of anhydrous ethanol and stir evenly at 60° C. to obtain a lauric acid ethanol solution;

[0034] 2) adding 18.75 g of deionized water to the lauric acid ethanol solution obtained in step 1), stirring at 60° C. for 3 min, and then ultrasonically dispersing at a temperature of 40 to 55° C. for 30 to 45 min to disperse the lauric acid ethanol solution into extremely small particles and uniformly mix them into water to obtain a low surface energy solution;

[0035] 3) pouring the low surface energy solution obtained in step 2) into a small stirrer containing 37.5 g of standard sand, stirring for 3 min, then adding 37.5 g of high belite aluminate sulfate cement, stirring at a low speed for 180 s, and then stirring at a high speed for 150 s to obtain a modified cement mortar (water-cement ratio and sand-binder ratio are 0.5 and 1, respectively), pouring into a mold, and vibrating to remove bubbles;

[0036] 4) After demoulding the sample obtained in step 3), the sample was cured in a standard curing room at 20° C. and a relative humidity of 90% for 72 hours, and then dried in air to form a super-hydrophobic cement mortar block.

[0037] The setting time of the mortar mixture was measured using a mortar setting time measuring instrument in accordance with standard JGJ70-2009. The initial setting time of the sample was measured to be 27 minutes, and the final setting time was 33 minutes.

[0038] The contact angle was measured using a contact angle meter, and the contact angle of the hydrophobic cement mortar block sample was found to be 147.9°.

[0039] The above-mentioned hydrophobic cement mortar block was placed on 600-mesh sandpaper, and the sandpaper was fixed. The lower surface of the sample slid at a constant speed at a pressure of 656 Pa and rubbed against each other for 20 m. The contact angle was 147.9°, which was almost unchanged.

[0040] Example 2

[0041] A method for preparing a fast-setting, low-cost, strong integral hydrophobic cement mortar, the preparation comprising the following steps:

[0042] 1) Dissolve 1.5875 g of lauric acid in 3.75 g of anhydrous ethanol and stir evenly at 60° C. to obtain a lauric acid ethanol solution;

[0043] 2) adding 18.75 g of deionized water to the lauric acid ethanol solution obtained in step 1), stirring at 60° C. for 3 min, and then ultrasonically dispersing at a temperature of 40 to 55° C. for 30 to 45 min to disperse the lauric acid ethanol solution into extremely small particles and uniformly mix them into water to obtain a low surface energy solution;

[0044] 3) pouring the low surface energy solution obtained in step 2) into a small stirrer containing 37.5 g of standard sand, stirring for 3 min, then adding 37.5 g of high belite aluminate sulfate cement, stirring at a low speed for 180 s, and then stirring at a high speed for 150 s to obtain a modified cement mortar (water-cement ratio and sand-binder ratio are 0.5 and 1, respectively), pouring into a mold, and vibrating to remove bubbles;

[0045] 4) After demoulding the sample obtained in step 3), the sample was cured in a standard curing room at 20° C. and a relative humidity of 90% for 72 hours, and then dried in air to form a super-hydrophobic cement mortar block.

[0046] The setting time of the mortar mixture was measured using a mortar setting time measuring instrument in accordance with standard JGJ70-2009. The initial setting time of the sample was measured to be 28.5 minutes, and the final setting time was 35 minutes.

[0047] The contact angle was measured using a contact angle meter, and the contact angle of the hydrophobic cement mortar block sample was found to be 153.2°.

[0048] The above-mentioned hydrophobic cement mortar block was placed on 600-mesh sandpaper, and the sandpaper was fixed. The lower surface of the sample slid at a constant speed at a pressure of 656 Pa and rubbed against each other for 20 m. The contact angle was 153.2°, which was almost unchanged.

[0049] Example 3

[0050] A method for preparing a fast-setting, low-cost, strong integral hydrophobic cement mortar, the preparation comprising the following steps:

[0051] 1) Dissolve 2.25 g of lauric acid in 3.75 g of anhydrous ethanol and stir evenly at 60° C. to obtain a lauric acid ethanol solution;

[0052] 2) adding 18.75 g of deionized water to the lauric acid ethanol solution obtained in step 1), stirring at 60° C. for 3 min, and then ultrasonically dispersing at a temperature of 40 to 55° C. for 30 to 45 min to disperse the lauric acid ethanol solution into extremely small particles and uniformly mix them into water to obtain a low surface energy solution;

[0053] 3) pouring the low surface energy solution obtained in step 2) into a small stirrer containing 37.5 g of standard sand, stirring for 3 min, then adding 37.5 g of high belite aluminate sulfate cement, stirring at a low speed for 180 s, and then stirring at a high speed for 150 s to obtain a modified cement mortar (water-cement ratio and sand-binder ratio are 0.5 and 1, respectively), pouring into a mold, and vibrating to remove bubbles;

[0054] 4) After demoulding the sample obtained in step 3), the sample was cured in a standard curing room at 20° C. and a relative humidity of 90% for 72 hours, and then dried in air to form a super-hydrophobic cement mortar block.

[0055] The setting time of the mortar mixture was measured using a mortar setting time measuring instrument in accordance with standard JGJ70-2009. The initial setting time of the sample was measured to be 29 minutes, and the final setting time was 36 minutes.

[0056] The contact angle was measured using a contact angle meter, and the contact angle of the hydrophobic cement mortar block sample was found to be 154.8°.

[0057] The above-mentioned hydrophobic cement mortar block was placed on 600-mesh sandpaper, and the sandpaper was fixed. The lower surface of the sample slid at a constant speed at a pressure of 656 Pa and rubbed against each other for 20 m. The contact angle was 154.8°, which was almost unchanged.

[0058] Comparative Example 1

[0059] An ordinary cement mortar block, the preparation method of which is as follows:

[0060] 1) Add 18.75 g of deionized water to 3.75 g of anhydrous ethanol, stir at 60° C. for 3 min, and then disperse by ultrasonic at 40 to 55° C. for 30 to 45 min to obtain a low surface energy solution;

[0061] 2) pouring the low surface energy solution obtained in step 1) into a small stirrer containing 37.5 g of standard sand, stirring for 3 min, then adding 37.5 g of high belite aluminate sulfate cement, stirring at a low speed for 180 s, and then stirring at a high speed for 150 s to obtain a modified cement mortar (water-cement ratio and sand-binder ratio are 0.5 and 1, respectively), pouring into a mold, and vibrating to remove bubbles;

[0062] 3) After demoulding the sample obtained in step 2), the sample was cured in a standard curing room at 20° C. and a relative humidity of 90% for 72 hours, and then dried in air to form an ordinary cement mortar block.

[0063] The setting time of the mortar mixture was measured using a mortar setting time measuring instrument in accordance with standard JGJ70-2009. The initial setting time of the sample was measured to be 29.5 minutes, and the final setting time was 36 minutes.

[0064] The contact angle was measured using a contact angle meter, and the contact angle of the ordinary cement mortar block was found to be 0°.

[0065] like Figure 6 As shown, from Figure 6 (a)-(c) It can be observed that the internal structure of Comparative Example 1 is dense at 1K×, 5K× and 10K× magnifications, and ettringite produced by cement hydration appears inside the drug of Comparative Example 1, and the needle-shaped ettringite is interwoven into a network and is relatively evenly distributed in the cement block; Figure 6 (e)-(g) show that the addition of lauric acid leads to many micron-sized holes inside the mortar block of Example 3, and these places are mostly interwoven needle-shaped calcium sulfonate, and calcium sulfonate and the pore system show obvious hierarchical structure, providing the multi-level roughness required for the super-hydrophobic surface, because the solution with low surface energy is first mixed with sand and adsorbed on the surface of the sand during the preparation process, and cement is more inclined to hydrate around the sand, so that the hydration products of more pores cover the surface of the sand, thereby improving the roughness of the sand. The sample test results of the examples and comparative examples show that the super-hydrophobic concrete provided by the example after adding lauric acid is formed with a multi-level rough structure, which is a necessary condition for the sample to realize the super-hydrophobic function. Under the above conditions, the surface and inner surface of the sample of Example 3 show good super-hydrophobicity, and the hydrophobic angle can reach 154.8 °.

[0066] In the comparative example 1, C4A3S reacts rapidly with gypsum to generate calcium sulfonate and aluminum hydroxide gel at the initial stage of hydration, thus showing obvious characteristics of rapid setting and hardening; while the setting time of the cement mortar modified with lauric acid in Example 3 will increase. The reason for this phenomenon may be that the addition of the hydrophobic agent inhibits the hydration reaction, and the lauric silicate generated by the reaction of lauric acid and calcium hydroxide may also cause a hydrophobic layer to form on the surface of the concrete, constituting a barrier to normal hydration. The initial setting and final setting times of the examples and comparative examples are slightly different. The addition of lauric acid will extend the initial setting and final setting times by 3-5 minutes, but they are both much shorter than the initial setting time of 90 minutes and the final setting time of 120 minutes of ordinary Portland cement, and the processability of the mortar is guaranteed.

[0067] like Figure 7As shown in the figure, the overall hydrophobicity of the mortar is evaluated by the water absorption experiment. The immersion water absorption rate of Example 3 can be reduced by nearly 77% compared with that of Comparative Example 1, indicating that the cement-based material modified by lauric acid effectively blocks water penetration and significantly improves the overall hydrophobicity. This is because sufficient hydrophobic groups from lauric acid are connected and fill the mortar blocks through esterification reaction, which reduces the surface energy of the mortar; and water droplets on the concrete surface are difficult to penetrate into the capillary pores due to the repulsion of the capillaries.

[0068] like Figure 8 As shown, fine sand and wet soil were used as pollutants, and methyl red dyed water was dropped on the surface of the hydrophobic mortar block to test the self-cleaning properties of the sample. Figure 8 The self-cleaning process of the Example 3 sample is shown. Figure 8 Once the water falls on the surface of the hydrophobic mortar, it will quickly roll down with the pollutants and leave an obvious cleaning mark on the mortar surface. This is because the mortar surface modified with lauric acid is in a Cassie-Baxter state, and it is difficult for water droplets to stay on the inclined mortar surface. Therefore, in the process of water droplets rolling down, sand and soil particles with higher surface energy will be adsorbed on the water droplets and taken away. The self-cleaning experiment shows that the medicine in Example 3 has good self-cleaning properties.

[0069] In summary, the method for preparing hydrophobic cement mortar described in the present invention has the advantages of simple preparation process, safe and environmentally friendly materials and reagents, low cost, good hydrophobic effect, etc., and has broad application prospects in hydraulic concrete protection.

[0070] The above description is only a preferred embodiment of the present invention, and does not limit the implementation mode and protection scope of the present invention. For those skilled in the art, it should be aware that all solutions obtained by equivalent substitutions and obvious changes made using the description and illustrations of the present invention should be included in the protection scope of the present invention.

Claims

1. A method for preparing a fast-setting, low-cost, strong integral hydrophobic cement mortar, characterized in that: The following steps are involved: 1) dissolving lauric acid in anhydrous ethanol and stirring uniformly to obtain a lauric acid ethanol solution; 2) adding deionized water to the lauric acid ethanol solution obtained in step 1), stirring at 60-65° C. for 3-5 minutes, and then ultrasonically dispersing at a temperature of 40-55° C. for 30-45 minutes to obtain a low surface energy solution; 3) pouring the low surface energy solution obtained in step 2) into a small stirrer filled with standard sand, stirring for a period of time, then adding high belite aluminate sulfate cement, stirring at a low speed for 180 to 210 seconds, and then stirring at a high speed for 120 to 150 seconds to obtain a modified cement mortar, pouring it into a mold, and vibrating to remove bubbles; 4) After demoulding the sample obtained in step 3), the sample is cured in a standard curing room at 20-25° C. and a relative humidity of 90-95% for 24-72 hours, and then dried in air to form a super-hydrophobic cement mortar block.

2. The preparation method according to claim 1, characterized in that: Step 3) The mass ratio of high belite aluminate sulfate cement to lauric acid and anhydrous ethanol in the cement mortar is 1:(0.04-0.06):(0.06-0.10), and the water-cement ratio of the cement mortar is 0.45-0.

50.

3. The preparation method according to claim 2, characterized in that: Step 3) The sand-to-binder ratio in cement mortar is 0.7-1.

4. A fast-setting, low-cost, strong integral hydrophobic cement mortar block, characterized in that: Prepared according to the preparation method according to any one of claims 1 to 3.

Citation Information

Patent Citations

  • Preparation method of high-hardness wear-resistant super-hydrophobic concrete

    CN107244847A

  • Anti-caking ceramic tile adhesive and preparation method thereof

    CN110204277A